FAKTOR-FAKTOR YANG MEMPENGARUHI PENYALAHGUNAAN ASET - Siti Mardiah; Jasman (KRISNA: Kumpulan Riset Akuntansi, 2021)
This research aims to examine the influence of pressure, opportunity, rationalization, capability and integrity toward asset misappropriation through fraud star approach in governmental institution. This research used random sampling method and quantitative research design. Primary data is gathered from government employees through questionnaire, whether ministry or non-ministry with 100 respondents. Descriptive statistics, multiple regression model and classical assumption are used to analyze the data. The result of this research showed that rationalization and capability have positive and significant influence on asset misappropriation. Meanwhile, pressure, opportunity and integrity have no influence on asset misappropriation.